2018
DOI: 10.1130/l730.1
|View full text |Cite
|
Sign up to set email alerts
|

Post-collisional Cenozoic extension in the northern Aegean: The high-K to shoshonitic intrusive rocks of the Maronia Magmatic Corridor, northeastern Greece

Abstract: The Maronia Magmatic Corridor is a NE-trending belt of Oligocene plutons that intrudes the Kechros Dome of the northern Rhodope Core Complex in northeastern Greece. The post-collisional magmatism transitions from early high-K calc-alkaline magmatism in the NE to a younger, shoshonitic phase in the SW. We use a full suite of whole-rock geochemical analyses, including rare earth elements, to show a shared metasomatized mantle source of the magmatism. Evidence of plagioclase saturation from the onset of crystalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 108 publications
4
27
0
Order By: Relevance
“…Radiometric dating for the monzodiorite yielded ages of 31.9 ± 0.5 Ma (Rb/Sr on biotite, [38]). Recently, Perkins et al [65] provided further geochronological data for the magmatic intrusion in the Kirki area (32.05 ± 0.07 Ma, U-Pb on zircon). Late, NNW-trending microgranite porphyry dikes ( Figure 2) crosscut the aforementioned magmatic rocks and comprise the final intrusive stage in the area [51].…”
Section: Geology and Description Of The Pagoni Rachi Prospectmentioning
confidence: 99%
“…Radiometric dating for the monzodiorite yielded ages of 31.9 ± 0.5 Ma (Rb/Sr on biotite, [38]). Recently, Perkins et al [65] provided further geochronological data for the magmatic intrusion in the Kirki area (32.05 ± 0.07 Ma, U-Pb on zircon). Late, NNW-trending microgranite porphyry dikes ( Figure 2) crosscut the aforementioned magmatic rocks and comprise the final intrusive stage in the area [51].…”
Section: Geology and Description Of The Pagoni Rachi Prospectmentioning
confidence: 99%
“…Recently, Perkins et al [28], extending previous studies of Del Moro et al [24], classified the magmatic rocks of the Maronia-Leptokarya corridor, into two, temporally and geochemically distinct, magmatic complexes, the Kassiteres-Leptokarya magmatic suite and the Maronia plutonic complex respectively. Both complexes comprise magmatic rocks with calc-alkaline to shoshonitic compositions and post-collisional affinities.…”
Section: Genetic Implicationsmentioning
confidence: 81%
“…The Leptokarya pluton, forms part of a NE-trending intrusive belt that includes the Kassiteres, Kirki, Leptokarya and Tris Vrisses intrusions ( Figure 1) and consists of quartz monzogabbros/monzodiorites predominantly along with tonalites and granodiorite [24,25,27,28]. Theses intrusive rocks are characterized by a medium-grained, granular to porphyritic texture consisting of plagioclase and variable amounts of pyroxene, amphibole, biotite and Fe-Ti oxides, with quartz and K-feldspar occurring as interstitial minerals.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…Available geochronological data for the monzodiorite yielded cooling ages of 31.9 ± 0.5 Ma (Rb/Sr on biotite [49]) and 32.6 ± 0.5 Ma ( 40 Ar/ 39 Ar on biotite [50]). Recently, Perkins et al [51] conducted a U-Pb zircon geochronological study on the Kassiteres magmatic suite, showing that magmatism occurred between 32.05 ± 0.02 and 32.93 ± 0.02 Ma. Previous studies in this area have shown that the granodiorite hosts the Konos Hill porphyry Mo-Cu-Re-Au porphyry prospect [22,26,27].…”
Section: Local Geologymentioning
confidence: 99%